Roll-to-Roll Deposition of Wide-Bandgap CsFAPbBr3 Perovskite Solar Cells in Ambient Air with Optimized Ink Formulation - Jafarzadeh, Farshad; Dong, Lirong; Jang, Dongju; Wagner, Michael; Koch, Giulio; Qiu, Shudi; Feroze, Sarmad; García Cerrillo, José; Brabec, Christoph; Di Carlo, Aldo; Brunetti, Francesca; Egelhaaf, Hans-Joachim; et al. (Solar RRL, 2024)
The growing demand for sustainable energy solutions has made the development of scalable, efficient, and cost-effective perovskite solar cells (PSCs) increasingly important. Wide-bandgap perovskites (WB-PSCs) stand out due to their efficiency in low-light conditions and their use in tandem solar cells. WB-PSCs are currently behind conventional PSCs in upscaling, with limited success in printing wide bandgap PSCs. Developing upscaling methods is essential to fully realize their potential in the renewable energy sector. This research addresses the development of roll-to-roll (R2R) slot-die coating of Cs0.05FA0.95PbBr3-based WB-PSCs by focusing on improving the film formation process and ink formulation. By adding optimal concentration of CsBr and performing in situ characterization, we obtained Cs0.05FA0.95PbBr3 films with enhanced morphology and crystallinity in ambient conditions (50% RH), without inducing secondary phase formation. In addition, slot-die coating defects are eliminated through introducing DMSO: Butanol (9:1) solvent system. The R2R coated wide-bandgap PSCs reaches a power conversion efficiency (PCE) of up to 8.97% under 1-sun conditions and 18.3% PCE under indoor conditions. The corresponding R2R coated modules with a 5 × 5 cm2 active area achieve a PCE of 5.8%, representing a crucial step towards the high-throughput, cost-effective production of perovskite solar modules.
CRIS-Team Scopus Importer:2024-10-11
Keywords: ambient deposition; ink formulation; roll-to-roll; slot-die coating; wide-bandgap perovskite solar cells